2020
DOI: 10.1029/2019je006312
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Evolution of the Evection Resonance/Quasi‐Resonance and the Angular Momentum of the Earth‐Moon System

Abstract: Forming the Moon by a high‐angular momentum impact may explain the Earth‐Moon isotopic similarities; however, the post‐impact angular momentum needs to be reduced by a factor of 2 or more to the current value (1 LEM) after the Moon forms. Capture into the evection resonance, occurring when the lunar perigee precession period equals 1 year, could remove the angular momentum excess. However the appropriate angular momentum removal appears sensitive to the tidal model and chosen tidal parameters. In this work, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Touma & Wisdom (1998) studied this regime and showed that capture into such a resonance could have been encountered for a M ≈ 4.6R E , exciting the lunar eccentricity to e ≈ 0.5. However, the timescale of capture and escape from this evection resonance is 10 4 ∼ 10 5 yr, after which the lunar orbit tends to circularization again (Rufu & Canup 2020).…”
Section: Appendix A: Orbital Dynamicsmentioning
confidence: 99%
“…Touma & Wisdom (1998) studied this regime and showed that capture into such a resonance could have been encountered for a M ≈ 4.6R E , exciting the lunar eccentricity to e ≈ 0.5. However, the timescale of capture and escape from this evection resonance is 10 4 ∼ 10 5 yr, after which the lunar orbit tends to circularization again (Rufu & Canup 2020).…”
Section: Appendix A: Orbital Dynamicsmentioning
confidence: 99%
“…For non-spinning planets, the range of satellite-producing impact angles is only a few degrees, but for spinning planets, wider ranges become feasible. In particular, a prograde spinning proto-Earth allows less disruption of Theia for viable satellite formation at lower angles, although high initial rotation rates may require some angular momentum to be removed from the final system (Rufu & Canup 2020).…”
Section: Immediate Satellite Formationmentioning
confidence: 99%
“…High angular momentum impacts into rapidly spinning targets ( Ćuk & Stewart 2012;Lock et al 2018) can eject and mix more proto-Earth material, as can a very large impactor (Canup 2012). The excess angular momentum might be removable in or near the evection resonance, but removing the correct amount may be difficult (Rufu & Canup 2020). Hit-and-run impacts can also make somewhat more target-rich disks (Reufer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While the total angular momentum of the bound material, a key constraint in case of the Moon forming GI (e.g., Canup 2004a), shows little variation for the two compared EOS and different resolutions, the Earth's post-impact rotation period affects the tidal interaction with the Moon. This in turn affects the Moon's outward migration rate and the efficiency of AM removal due to evection resonances (Rufu & Canup 2020), a key mechanism in reconciling high AM Moon forming impacts with observations (Canup 2012;Ćuk & Stewart 2012;Lock et al 2018). The impact conditions that lead to erosion of a proto-planet or smaller body are characterised by the value of 𝑄 * RD and play a crucial role in determining many important properties of the final planetary system like the final number of planets, their mass and bulk composition.…”
Section: Discussionmentioning
confidence: 99%